2018
DOI: 10.1039/c7cp08387d
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-dependent phase evolution of copper-oxide thin-films on Au(111)

Abstract: The formation of ultrathin copper oxide layers on an Au(111) surface is explored with scanning tunneling microscopy and density functional theory. Depending on the thermal treatment of as-grown Cu-O samples, a variety of thin-film morphologies is observed. Whereas 1D oxide stripes with Au[112[combining macron]] and Au[11[combining macron]0] orientation emerge at 450 and 550 K annealing, respectively, a planar (2 × 2) Cu-O network with specific domain structure develops at higher temperature. The latter is ascr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 37 publications
3
35
1
Order By: Relevance
“…The oxide film is permeated by dislocation lines, compensating for the misfit strain with the gold support. Depending on thickness and thermal treatment of the Cu 2 O layer, the domain boundaries adopt triangular, zig-zag and straight configurations [23]. The films prepared here are composed of triangular domains with 5 nm edge length.…”
Section: Experimental Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…The oxide film is permeated by dislocation lines, compensating for the misfit strain with the gold support. Depending on thickness and thermal treatment of the Cu 2 O layer, the domain boundaries adopt triangular, zig-zag and straight configurations [23]. The films prepared here are composed of triangular domains with 5 nm edge length.…”
Section: Experimental Techniquesmentioning
confidence: 99%
“…Rising the temperature to 700 K finally destroys the oxide film and renders the pristine Au(111) surface visible in the STM. The oxide decomposition is driven by Cu dissolution into the Au support, associated with oxygen desorption from the surface [23]. The peculiar electronic structure of ML Cu islands on Cu 2 O/Au(111) is addressed in the following paragraph.…”
Section: Experimental Techniquesmentioning
confidence: 99%
“…The same honeycomb structure has also been found in the copper oxide Cu 3 O 2 ML, which forms on Au(111). 19 We have recently shown that the low dimensionality of freestanding M 2 O 3 monolayers, associated with their peculiar, perfectly flat atomic structure, is responsible for their specific electronic characteristicschange in the degree of covalency and in the gap width, orbital reconstruction, and new spin ordering compared to their bulk counterpartsand that the same is true for MLs of mixed MM′O 3 composition. 20 Since M 2 O 3 monolayers cannot be exfoliated, the question arises as to how the specific properties displayed by freestanding MLs are preserved in an experimentally achievable context, that is, when the MLs are deposited/grown on a substrate.…”
Section: Introductionmentioning
confidence: 99%
“…However, this is unlikely to be the case for honeycomb M 2 O 3 structures synthesized on metals due to a stronger oxide/substrate interaction. Simulations of such systems include V 2 O 3 on Pd(111) [22,23], Ti 2 O 3 [5] and FeWO 3 [19] on Pt(111), and M 2 O 3 (M = Sc, Ti, V, Cr, Mn, Fe, Co, Ni) [16,23,24] or Cu 3 O 2 [25] on Au(111). The honeycomb structure is a fully coordinated network consisting of hexagonal rings which can be used as a template for the adsorption of metal atoms, and a novel ternary oxide of Ba x Ti 2 O 3 was grown using this method [14].…”
Section: Introductionmentioning
confidence: 99%